Analisis Wacana Kritis Trash-talk Pada Konten Game Mobile Legends Di Kanal Youtube Gerrard Wijaya - Ferdyanto Tantyo Nugroho; Syafrida Nurrachmi Febriyanti (Peneliti.net, 2023)
The use of Trash-talk on the Youtube platform or in the play environment of generation Z youth is a phenomenon that is commonly seen, but it is interesting to see the use of Trash-talk which was originally a ban for parents to their children but has become normalized in the surrounding environment. The data collection technique was carried out by means of documentation studies and observations of Game Content entitled